Вплив технологічних режимiв гарячого штампування на структуру та властивості порошкових інтерметалідів Fe₃Al - Баглюк, Г. А.; Толочин, О. І.; Толочина, О. В.; Яковенко, Р. В. (НТУ "ХПІ", 2014)
Приведені результати дослідження можливостей застосування технології гарячого штампування пористих заготовок (ГШПЗ) для одержання Fe₃Al інтерметалідів i впливу режим1в штампування та наступної термiчної обробки на структуру i властивостi останніх. Порошки Fe₃Al iнтерметалiду одержували термiчним синтезом при 1000°С у вакуумi iз сумiшi елементарних порошкiв Fe i Al. Гаряче штампування спресованих заготовок проводили при 1000, 1050, 1100 i 1150°С і піддавали гарячештампованi зразки додатковому спiканню у вакуумi в дiапазонi температур 1100÷1450°С. Спiкання гарячештампованих зразкiв призводить до збільшення мiцностi i трiщиностiйкостi матерiалiв, тодi як твердiсть гарячештампованих інтерметалідів знижується пiсля спiкання останнiх.

The capabilities of powder hot forging for manufacturing of Fe₃Al intermetallics and effect of forging and following thermal treatment routines on their structure and properties had been investigated. Fe₃Al intermetallic powders were produced by means of thermal synthesis at 1000 °С in vacuum from a mixture of Fe and Al elemental powders. Hot forging of consolidated preforms had been carried out from 1000, 1050, 1100 and 1150°С and afterwards the hot forged preforms were subjected to supplementary sintering in vacuum at 1100-1450°C It is foud, that thermal synthesis of Fe + 14 % Al powder mixture results in formation of FeAl phase, which remains after hot forging too, but using of supplementary sintering for hot forged specimens makes it possible to ensure intermetallics structure ordering with formation of Fe₃Al predominant pfase. Sintering of hot forged specimens result in increasing of strength and crack growth resistance, which values enhance with increasing of sintering temperature. Otherwise the hardness of hot forged intermetallics decreases after their sintering. The best comlex of mechanical properties, namely -bending strength - 1030 MPa, crack growth resistance - 32 MPa-m1/2, Vickers hardness - 2300 MPa, have the intermetallics, produced by means of hot forging and supplementary sintering at 1450°С.
Effect of hot forging on structure and properties of powder Fe₃Al intermetallics
Keywords: iнтерметалiд; алюмiнiд залiза; порошок; гаряче штампування; спікання; структура; міцність; intermetallics; iron aluminides; powder; hot forging; sintering; structure; strength